Equine congenital heart disease and respiratory disease interactions. (4th March 2019) - Navas De Solis, C.; Wesselowski, S.
Summary: The interactions between the respiratory and cardiovascular system in neonates with severe illness are relevant to the equine clinician. There is little information available regarding the treatment of congenital heart disease or pulmonary hypertension in foals, thus a team approach with experts in these fields may help our equine cases.